Incentives and impacts: dissecting individual and collective cheating in organizations - Riyanto, Yohanes Eko (2024)
In collective decisions, cheating benefits may be independent of others' choices, while the harm to recipients depends on the group outcome, or both benefit and damage rely on the collective outcome. We explored how individuals act in these scenarios through a lab experiment where three participants sequentially reported a coin toss outcome, affecting passive recipients based on the majority's dishonesty. Our findings indicate that when both the harm and benefits depend on the group's outcome, participants strategically choose their responses. They are honest when their deception cannot change the group's decision but more likely to cheat for a higher collective benefit. However, when their gain is tied only to their own actions, hiding their intent to cheat is futile, leading to consistent cheating behavior regardless of its impact on the group. Interestingly, participants were more hesitant to cheat if it harmed just one person, but only when their benefits were not tied to the group outcome. This study sheds light on the complex dynamics of cheating in group settings and the moral calculations behind individuals' choices.